A review of selected aspects of big data usage in banks’ risk management - Dvorski Lacković, Ivana (Array, 2020)
Contemporary banks operate in a changing environment influenced by regulatory requirements, emerging new risk types and high competition on the market. At the same time banks have on their disposal large datasets from internal and external sources – the question arising is whether banks are using adequate analytics to gain value from big data. Big data has been used in banking for some time, mostly in the marketing field, but the usage of big data in banks’ risk management has not been a subject of extensive scientific research. The goals of this paper are twofold. Firstly, the authors are presenting an overview of existing research on the topic of big data usage in banks’ risk management by discussing selected aspects of this topic. Secondly, the authors are formulating a proposal on how to strategically use big data in risk management in banks by merging literature based extracted usage of big data with risk management phases. Expected contributions of this paper are systematization of knowledge from available literature and increasing scientific and professional awareness on the topic and potential of big data in banks’ risk management.